Mayo Clinic family health book - Litin, Scott C.; Mayo Clinic (New York : HarperResource, 2003)
A complete medical reference guide for the entire family, covering health aspect through the years, staying well, first aid and emergency care, human diseases and disorders, and modern medical care.
"Completely revised and updated"--Dust jacket.
Includes index.
Booklist.
Adult
Keywords: Medicine, Popular; Popular medicine; Medicine -- Encyclopedias -- English; Medicine -- Popular Works